LEGAL INSTRUMENT FOR PROTECTION OF GEOGRAPHICAL INDICATION PRODUCT IN INDONESIA - Nansa, Almusawir (Journal of Humanity, 2013)
As an archipelago country, Indonesia comprises of a large territory where every region is capable of producing distinctive and characterized products due to its geographical, social, and cultural factors, in addition to its higher quality compared to imported products. In the market, goods with distinct characterization as a result of various geographical locations of production regions is known as Geographical Indication Products. Geographical Indication defines as a characterization that indicates the origin of a product, which includes several influencing factors such as geographical factor, natural factor, human factor or the combination of both factors which eventually contribute to establish a certain distinction and quality upon a product. Several geographical indicated products in Indonesia are widely known to have excellent reputation on the market, namely Delinese tobacco, Temanggung tobacco, Ciancur rice, Muntok white pepper, Lampung black pepper, Kerinci cinnamon, Cilembu cassava, Bandanese nutmeg, Proboliggo sweet mango, Balinese Kintamani coffee, Kalosi coffee, Papuan matoa, etc. Those are several richness of goods from certain regions in Indonesia widely known for their characterization. Characterization of goods are resulted by variation of geographic locations of producing regions in Indonesia. These goods possess high quality and high economic value. Consequently, certain instruments are required to provide protection upon the regions producing those goods against the act of counterfeiting.